PEMENUHAN HAK LAYANAN KUNJUNGAN NARAPIDANA PADA ERA NORMAL BARU DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIA KEROBOKAN - Anindi, Dewa Ayu Putu Sadwi; Suryana, Kadek Dedy; Mahadewi, I Gst. Agung Ika Laksmi (CV Widina Media Utama, 2023)
The purpose of the research in this paper is to analyze the arrangements for fulfilling the rights of visiting services for prisoners before and after the new normal era and the obstacles faced at the Women's Correctional Institution Klas IIA Kerobokan. This research uses empirical legal research. The research method used is descriptive by using qualitative data analysis techniques. The data required are primary data and secondary data. Primary data includes the results of observations, distribution of questionnaires to prisoners, and interviews with the Head of the Prison Security Unit (Ka.KPLP), Head of Minkamtib Section, Head of Binadik Section and prisoners related to the fulfillment of the rights of visiting services for prisoners in the Women's Prison Klas IIA Kerobokan. While secondary data is data sourced from library materials intended to help complement various legal concepts in primary legal materials. The results showed that the fulfillment of the right of visiting services for prisoners in the new normal era at the Klas IIA Kerobokan Women's Prison has been carried out in accordance with applicable regulations, however, due to the COVID-19 pandemic which requires adjustments to the rules of face-to-face visiting services to online visiting services during the pandemic and limited face-to-face visiting services in the new normal era, the fulfillment is felt to be less than optimal by prisoners.ABSTRAKTujuan penelitian dalam penulisan ini untuk menganalisis pengaturan pemenuhan hak layanan kunjungan narapidana sebelum dan sesudah era normal baru serta kendala yang dihadapi di Lembaga Pemasyarakatan Perempuan Klas IIA Kerobokan. Penelitian ini menggunakan jenis penelitian hukum empiris. Metode penelitian yang digunakan adalah deskriptif dengan menggunakan teknik analisa data secara kualitatif. Data yang diperlukan adalah data primer dan data sekunder. Data primer meliputi hasil observasi, pembagian kuesioner kepada narapidana, dan wawancara terhadap Kepala Kesatuan Pengamanan Lapas (Ka.KPLP), Kasi Minkamtib, Kasi Binadik dan narapidana terkait pemenuhan hak layanan kunjungan narapidana di Lapas Perempuan Klas IIA Kerobokan. Sedangkan data sekunder merupakan data yang bersumber dari bahan-bahan kepustakaan yang ditujukan untuk membantu melengkapi berbagai konsep hukum pada bahan hukum primer. Hasil penelitian menunjukkan pemenuhan hak layanan kunjungan narapidana pada era normal baru di Lapas Perempuan Klas IIA Kerobokan sudah dilaksanakan sesuai dengan aturan yang berlaku, akan tetapi akibat pandemi COVID-19 yang mengharuskan adanya penyesuaian aturan layanan kunjungan tatap muka menjadi layanan kunjungan online pada masa pandemi serta layanan kunjungan tatap muka terbatas pada era normal baru dalam pemenuhannya dirasakan kurang maksimal oleh narapidana.